Capital's Next Five Years' Delhi's Prospective Eighth Five Year Plan 1992-97 and Annual Plan 1992-93 Volume-I Delhi Administration - Planning Commission (Planning Commission, 1992)
The 'Directional Paper' for the Eighth Five year Plan prepared by the Planning Commission setting out the objectives, thrusts and macroeconomic dimensions of the Eighth Plan has been carefully followed while formulating Delhi's Eighth Five Year Plan proposals. In tune with the overall contents of the directional paper we hold the view that the Nineties of Delhi will be progressively needing a realistic, long sustaining and growth oriented Eighth Five Year Plan to cope up with the pressing realities of the Capital. Marching ahead with purposeful development measures with concomitant economic reforms will be the expected trend.
Planning Department